Knowledge, attitudes and practice of breast cancer screening among female personnel of Walailak University - Manas Kotepui (2018)
© 2015 John Wiley & Sons Ltd. Background: Breast cancer is the most common cancer among women worldwide. Methods: This study aimed to assess the knowledge, awareness and practice of breast cancer screening for early detection of breast cancer among female personnel at a university. A cross-sectional descriptive study was administered to female personnel of Walailak University in Nakhon Si Thammarat, Thailand. Data were analysed by SPSS version 16. Results: Among total of 217 female personnel, the lecturers and laboratory scientists and general officers had a significantly higher mean knowledge score about the practice of breast cancer screening than temporary employees (P < 0.0001). The level of education and income of respondents may be involved with this difference in knowledge (P < 0.05). Conclusion: This study concludes that knowledge about the practice of breast cancer screening could be attributed to different career groups, level of education and income of respondents. There is a very urgent need for regular learning courses for personnel concerning knowledge about the practice of breast cancer screening especially for those personnel with less formal education and low income.